(untitled) (Global Journal of Management and Business Research, 2020)
The central role that the manager plays in the decision-making process within small and medium-sized enterprises (SMEs) is a fruitful field of research to study his perception of the concept of CSR. Not with standing the abundant literature devoted to CSR, especially in SMEs, empirical research dedicated to the perception of the "top managment" of these structures, specifically in the African context, remains very limited. Based on the assumption that forest certification is likely to be a distinctive variable in the perception of CSR, a qualitative study was conducted among the strategic actors of four Cameroonian SMEs in the forest industry, two of which Forest Stewards hip Council (FSC) certified and two uncertified reveals (1) a small distinction between the two groups in terms of their knowledge and appropriation of the concept of CSR, (2) the identification of motivations but above all (3) the brakes to the commitment of the organization.